An Analysis of Influencing Risk Models of Elderly Abuse - Timalsina, Keshab Prasad (International Research Journal of MMC, 2022)
The elderly abuse recognizing to be a substantial and growing public health problem worldwide. The present study aims to analyse the risk factors of elderly abuse in family environment of Nijgadh Municipality. A descriptive cross-sectional study has been carried out among 204 elders taken from the community through simple random sampling method. The data were collected through face to face structured interview schedule in 2021. The binary logistic regression model was created as statistical analysis. The result of the study revealed that the elders who lived without spouse were 6.221 times more likely to be abused than those who lived with partners. Followed by functional disability of elders (elders with disability were 2.277 times higher than no disability), etc. This study created 5 models of risk factors among which model 2 had explained variation (24.6%) than others. This study found that living without a spouse, dependency, poor health, having fewer family members and the aging of seniors are the most common reasons for being abused in a family environment. This research has produced data on the odds ratio of elderly abuse based on many socio-demographic factors, which can be utilized to identify and protect elders who are at high risk of abuse through multi-sectoral social justice action.